Differentiation of endospheric microbiota in ancient and modern wheat cultivar roots - Solène Mauger; Claire Ricono; Cendrine Mony; Vèronique Chable; Estelle Serpolay; Marine Biget; Philippe Vandenkoornhuyse (Plant-Environment Interactions, 2021)
Abstract Modern plant breeding and agrosystems artificialization could have altered plants’ ability to filter and recruit beneficial microorganisms in its microbiota. Thus, compared to modern cultivars, we hypothesized that root‐endosphere microbiota in modern wheat cultivars are less resistant to colonization by fungi and bacteria and thus more susceptible to also recruit more pathogens. We used an in‐field experimental design including six wheat varieties (three ancient vs. three modern) grown in monoculture and in mixture (three replicates each). Endospheric microbiota of wheat roots were analyzed on four individuals sampled randomly in each plot. Composition‐based clustering of sequences was then characterized from amplicon mass‐sequencing. We show that the bacterial and fungal microbiota composition in wheat roots differed between ancient and modern wheat cultivar categories. However, the responses observed varied with the group considered. Modern cultivars harbored higher richness of bacterial and fungal pathogens than ancient cultivars. Both cultivar types displayed specific indicator species. A synergistic effect was identified in mixtures of modern cultivars with a higher root endospheric mycobiota richness than expected from a null model. The present study shows the effect of plant breeding on the microbiota associated plant roots. The results call for making a diagnosis of the cultivar's endospheric‐microbiota composition. These new results also suggest the importance of a holobiont‐vision while considering plant selection in crops and call for better integration of symbiosis in the development of next‐generation agricultural practices.